Consuming Olympism: Consumer culture, sport star sponsorship and the commercialisation of the Olympics. (May 2018) - Smart, Barry
The roots of Olympism lie in the late 19th century and Baron Pierre de Coubertin's revival of the Olympic Games. The values of Olympism have been increasingly compromised by subsequent developments which have significantly transformed modern sport. Professionalism, commercialism, proliferating forms of spectacular media representation and a globalising consumer culture have transformed the Olympic Games and reduced the values of Olympism to marketing rhetoric. The summer Olympic Games in particular have become unrivalled marketing opportunities for host cities, consumer brands, and participating athletes, for whom the prospect of sporting success now promises to deliver wealth, stardom, and iconic global status beyond track and field. The complex forms of articulation of the Olympics with consumer culture are at the heart of the article which gives critical consideration to (1) the increasing commercialisation of the Olympic Games, (2) the growth of Olympic merchandising and (3) a comparison of the athletic performances, profiles, and consumer sponsorship statuses of three generations of iconic Olympic sprinters, Jesse Owens, Carl Lewis, and Usain Bolt, confirming in conclusion that the Olympic Games is immersed within and infused by a pervasive consumer culture.